Sound Field Analysis Based on Analytical Beamforming. (26th November 2006) - Guillaume Guillaume, M. M.; Grenier Grenier, Y. Y.
Abstract : The plane wave decomposition is an efficient analysis tool for multidimensional fields, particularly well fitted to the description of sound fields, whether these ones are continuous or discrete, obtained by a microphone array. In this article, a beamforming algorithm is presented in order to estimate the plane wave decomposition of the initial sound field. Our algorithm aims at deriving a spatial filter which preserves only the sound field component coming from a single direction and rejects the others. The originality of our approach is that the criterion uses a continuous instead of a discrete set of incidence directions to derive the tap vector. Then, a spatial filter bank is used to perform a global analysis of sound fields. The efficiency of our approach and its robustness to sensor noise and position errors are demonstrated through simulations. Finally, the influence of microphone directivity characteristics is also investigated.